Strategi Kebijakan Kementerian Agama dalam Mencegah Perkawinan Anak di Wilayah Rawan: Studi Kasus Sulawesi Tenggara - Tanaka, Ahmad (JURNAL ILMIAH GEMA PERENCANA, 2025)
Abstract This article analyzes the persistence of child marriage in Southeast Sulawesi, highlighting the gap between legal commitments and on-the-ground realities, and identifying the absence of comprehensive programs from religious institutions in changing conservative views as a crucial root cause. This condition, exacerbated by literal religious justifications and marriage dispensation loopholes, seriously threatens children's fundamental rights and hinders sustainable development efforts. This study employs a descriptive-analytical qualitative approach, based on extensive literature review and document analysis. The primary problem was identified using USG (Urgency, Seriousness, Growth) analysis. Furthermore, root cause identification utilized the Fishbone Theory, and policy alternative selection was guided by William N. Dunn's Policy Analysis Theory. The analysis results show that the dominance of conservative views, without progressive intervention from religious institutions, reinforces child marriage practices, worsened by dispensation loopholes and limited capacity of religious counselors. The discussion links these findings with Social Cognitive Theory, Theory of Planned Behavior, Policy Implementation Gap Theory, and Legal and Social Conflict Theory, emphasizing the urgency of religious moderation (moderasi beragama), maqasid syariah, and a Whole-of-Government approach. In conclusion, the core issue lies in the sub-optimal role of the Ministry of Religious Affairs as a religious authority in shifting societal perspectives. The most relevant policy recommendation is the issuance of a Ministerial Regulation (PMA) to mainstream child marriage prevention as a Key Performance Indicator (KPI) for all Ministry of Religious Affairs units, supported by strengthening counselor capacity and multi-stakeholder collaboration, to ensure equitable legal protection for children.